Economic burden and health-related quality-of-life among infants with respiratory syncytial virus infection: A multi-country prospective cohort study in Europe. Issue 16 (17th April 2023) - Mao, Zhuxin; Li, Xiao; Dacosta-Urbieta, Ana; Billard, Marie-Noëlle; Wildenbeest, Joanne; Korsten, Koos; Martinón-Torres, Federico; Heikkinen, Terho; Cunningham, Steve; Snape, Matthew D.; Robinson, Hannah; Pollard, Andrew J.; et al.
Highlights: We collected daily data to assess the impact of RSV on infants and caregivers. RSV quality of life loss was substantial, irrespective of medical attendance. The quality of life loss in a caregiver trailed that of their infant with RSV. Costs varied by country and were negligible for non-medically attended RSV. Abstract: Background: Respiratory syncytial virus (RSV) causes a considerable disease burden in young children globally, but reliable estimates of RSV-related costs and health-related quality-of-life (HRQoL) are scarce. This study aimed to evaluate the RSV-associated costs and HRQoL effects in infants and their caregivers in four European countries. Methods: Healthy term-born infants were recruited at birth and actively followed up in four European countries. Symptomatic infants were systematically tested for RSV. Caregivers recorded the daily HRQoL of their child and themselves, measured by a modified EQ-5D with Visual Analogue Scale, for 14 consecutive days or until symptoms resolved. At the end of each RSV episode, caregivers reported healthcare resource use and work absenteeism. Direct medical costs per RSV episode were estimated from a healthcare payer's perspective and indirect costs were estimated from a societal perspective. Means and 95% confidence intervals (CI) of direct medical costs, total costs (direct costs + productivity loss) and quality-adjusted life-day (QALD) loss per RSV episode were estimated per RSV episode, as well as per subgroup (medical attendance, country). Results: Our cohort of 1041 infants experienced 265 RSV episodes with a mean symptom duration of 12.5 days. The mean (95% CI) cost per RSV episode was €399.5 (242.3, 584.2) and €494.3 (317.7, 696.1) from the healthcare payer's and societal perspective, respectively. The mean QALD loss per RSV episode of 1.9 (1.7, 2.1) was independent of medical attendance (in contrast to costs, which also differed by country). Caregiver and infant HRQoL evolved similarly. Conclusion: This study fills essential gaps for future economic evaluations by prospectively estimating direct and indirect costs and HRQoL effects on healthy term infants and caregivers separately, for both medically attended (MA) and non-MA laboratory-confirmed RSV episodes. We generally observed greater HRQoL losses than in previous studies which used non-community and/or non-prospective designs.